Writing short stories to describe literary language use and perceptions as writer - Hernández Martín, José Alonso (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This qualitative case study aims at describing the process followed by ninth grade students at a private religious school when using and analyzing literary language. The instruments used to carry out this study were: students’ artifacts to identify and analyze the literary language used, field notes, and interviews. During this process, the learners as authors generated the construction of meaning and developed their competence in writing. The results show that students used metaphors and similes (literary features) to express ideas and details about their contexts in written production. In turn, students profited from the poetic function of the language where their voices as authors describe their perceptions and experiences as writers.